PENGARUH PENDAPATAN ASLI DAERAH DAN DANA ALOKASI UMUM TERHADAP BELANJA MODAL PADA KABUPATEN/KOTA DI PROVINSI JAMBI - Eva Futri; Novi Mubyarto; Efni Anita (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2022)
This study aims to determine whether there is an effect between local revenue and general allocation funds on capital expenditures in regencies / cities in Jambi Province. The population in this study were all regencies/cities in the Jambi Province. The data used is secondary data taken from reports on the Realization of District / City Orchids in Jambi Province from 2017 to 2019. The sample in this study is 11 regions in districts and cities in Jambi Province, so the number of data tested for 3 years is 33 data. . The data analysis technique used in this research is Multiple Linear Analysis. The results showed that partially local revenue has an effect on capital expenditure while general allocation funds have no effect on capital expenditure. This study also shows that simultaneously local revenue and general allocation funds have an effect on capital expenditure.